Undifferentiated embryonal sarcoma of the liver in an adult patient - Lee, Kyu Ho (Clin Mol Hepatol, 2016)
Undifferentiated embryonal sarcoma of the liver (UESL) is rare primary hepatic sarcoma and is known to occur in pediatric patients. This case is the UESL occurred in a 51-year old male patient. Multilocular cystic lesion was composed of primitive spindle cells without specific differentiation. This rare case would help to review differential diagnosis of primary sarcoma in liver and cystic neoplasm of the liver.